2016
DOI: 10.1590/1413-812320152110.224720
|View full text |Cite
|
Sign up to set email alerts
|

Fatores relacionados à qualidade de vida de pais de crianças com deficiência auditiva

Abstract: Hearing loss among children, particularly those with severe and profound hearing impairment, has an effect on their communication and development, which in turn can have a significant impact on their parents. This study aimed to evaluate the quality of life of parents of children with hearing loss and identify the associated factors. A cross-sectional study was carried out involving parents of children that went through phonoaudiological therapy at a public university clinic in the city of São Paulo. The resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
5
0
4
Order By: Relevance
“…protection, home environment, financial resources, health and social care, including availability and quality, opportunity to acquire new information and skills, participation and recreation/leisure opportunities, and the physical environment including pollution, noise, traffic, weather and transportation.Another study with parents of hearing-impaired children, using the same questionnaire tool, also verified that the environmental domain of WHOQOL-bref was the most compromised[6]. This aspect is related to the housing and health conditions of the G1 group, especially the availability of transportation to take the child to the appointments.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…protection, home environment, financial resources, health and social care, including availability and quality, opportunity to acquire new information and skills, participation and recreation/leisure opportunities, and the physical environment including pollution, noise, traffic, weather and transportation.Another study with parents of hearing-impaired children, using the same questionnaire tool, also verified that the environmental domain of WHOQOL-bref was the most compromised[6]. This aspect is related to the housing and health conditions of the G1 group, especially the availability of transportation to take the child to the appointments.…”
mentioning
confidence: 72%
“…Our study evaluated the QL of the mothers of children with microcephaly due to the increasing number of cases in Brazil and in other countries, and the impact that the disease causes on the life of these mothers. Previous studies have evaluated the QL of parents or caretakers of children with developmental disabilities or disorders such as autism, Down's syndrome and cerebral palsy [6,10,11], but no studies on the QL of the mothers of children with microcephaly were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura apresenta alguns estudos que versam sobre as consequências dessas concentrações de profissionais e também de serviços (JARDIM et al, 2017;TEIXEIRA, 2007;ALVARENGA et al, 2011;RAMIRES;BRANCO-BARREIRO;PELUSO, 2016). A conclusão desses autores é que apesar da qualidade considerada positiva dos serviços prestados, ainda sim existe a dificuldade de acesso.…”
Section: Discussionunclassified
“…Um estudo realizado por Ramires et al (2016) visando avaliar a qualidade de vida de pais de crianças com deficiência auditiva e verificar os fatores associados, concluiu que a qualidade de vida dos pais de crianças com deficiência auditiva bilateral de grau severo e/ou profundo foi comprometida com aspectos relacionados ao meio ambiente e psicológicos.…”
Section: Discussionunclassified